Impact of COVID-19 on Green Financial Practices of Banks and Financial Institutions in Bangladesh - Moon, Zarin Khan; Hasan, Md. Mahedi (Journal of Business and Social Sciences Research, 2022)
Bank and financial institutions (FIs) as environmentally friendly and socially responsible institutions plays important role in balancing sustainable economic development and environmental conservation through green financing guided by Bangladesh Bank (BB). COVID 19 has kept an adverse effect on the whole economy and economic system. The aim of this study was to see whether COVID-19 has any impact on the green performance of bank and financial institutions. Secondary data from the Bangladesh Bank was collected through document analysis and a qualitative analysis was made. It was seen that COVID-19 affected most of the sectors of the green activities of bank and Financial Institutions. Time befitting policies should be taken by the government and Bangladesh Bank to get rid of these effects.